New Insights and Challenges Associated With IgA Vasculitis and IgA Vasculitis With Nephritis—Is It Time to Change the Paradigm of the Most Common Systemic Vasculitis in Childhood? - Jelusic, Marija; Sestan, Mario; Giani, Teresa; Cimaz, Rolando (Frontiers in Pediatrics, 2022)
What are the challenges ahead and how have we responded so far when it comes to the non-granulomatous systemic vasculitis, characterized mainly by deposits of IgA immune complexes in the endothelium of small blood vessels - IgA vasculitis (IgAV)? That is the question to which we tried to answer. We summarized existing knowledge about epidemiology, pathogenesis, genetics, diagnostic tests and therapy in this somewhat neglected entity in pediatric rheumatology. Since etiopathogenesis of IgA vasculitis is complex, with factors other than galactose-deficient IgA1-containing immune complexes also being important, and may involve numerous interactions between environmental and genetic factors, genomics alone cannot explain the entirety of the risk for the disease. The incidence of IgAV and nephritis varies worldwide and may be a consequence of overlapping genetic and environmental factors. In addition to the role of the HLA class II genes, some studies have pointed to the importance of non-HLA genes, and modern geostatistical research has also indicated a geospatial risk distribution, which may suggest the strong influence of different environmental factors such as climate, pathogen load, and dietary factors. The application of modern geostatistical methods until recently was completely unknown in the study of this disease, but thanks to the latest results it has been shown that they can help us a lot in understanding epidemiology and serve as a guide in generating new hypotheses considering possible environmental risk factors and identification of potential genetic or epigenetic diversity. There is increasing evidence that an integrative approach should be included in the understanding of IgA vasculitis, in terms of the integration of genomics, proteomics, transcriptomics and epigenetics. This approach could result in the discovery of new pathways important for finding biomarkers that could stratify patients according to the risk of complications, without an invasive kidney biopsy which is still the gold standard to confirm a diagnosis of nephritis, even if biopsy findings interpretation is not uniform in clinical practice. Ultimately, this will allow the development of new therapeutic approaches, especially important in the treatment of nephritis, for which there is still no standardized treatment.